A gas path fault diagnostic model of gas turbines based on changes of blade profiles. (January 2020) - Zhou, Dengji; Wei, Tingting; Huang, Dawen; Li, Yuanfu; Zhang, Huisheng
Highlights: A novel gas path diagnostic model considering blade profile changes is established. Effects of blade profiles on physical fields and component performance are analyzed. The simulation experiments and field data analysis validate the diagnostic model. Abstract: The health conditions of blades directly affect the conversion efficiency and service life of the whole equipment. It is an effective way to establish the gas path diagnostic model of gas turbines for real-time monitoring, troubleshooting, and prevention, to improve equipment management. There are usually two tasks to diagnose gas path faults: (I) defining the gas path fault indexes and establishing mapping relationship between indexes and monitoring parameters, (II) solving reverse problem, namely, calculating fault indexes by the monitoring parameters. Current research mainly focuses on task (II), but neglects task (I). In addition, the diagnostic results based on thermodynamic parameters fluctuate greatly, and it is difficult to support actual maintenance. The blade profile change parameters are used to replace the traditional performance degradation parameters to realize gas path fault diagnosis. The typical gas path deterioration is characterized by the blade profile change parameters, including the blade thickness increment and blade roughness. Further, the velocity, temperature, and pressure fields are obtained by numerical simulation. Moreover, the effects of blade profile change parameters on stage and component performance maps are analyzed to establish a novel degradation simulation model. Based on the above analysis, the diagnostic model is applied to simulation experiment and used to process the field data of a faulty gas turbine. The results indicate that the proposed diagnostic model is effective in gas path fault detection, in order to protect the engines, ensure safe and stable operation, and monitor the deterioration rate.